2021
DOI: 10.3390/ph14100963
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Ezrin on the Cell Surface Plasma Membrane Localization of Programmed Cell Death Ligand-1 in Human Choriocarcinoma JEG-3 Cells

Abstract: Immune checkpoint blockade (ICB) antibodies targeting programmed cell death ligand-1 (PD-L1) and programmed cell death-1 (PD-1) have improved survival in patients with conventional single agent chemotherapy-resistant gestational trophoblastic neoplasia (GTN). However, many patients are resistant to ICB therapy, the mechanisms of which are poorly understood. Unraveling the regulatory mechanism for PD-L1 expression may provide a new strategy to improve ICB therapy in patients with GTN. Here, we investigated whet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 61 publications
1
13
0
Order By: Relevance
“…Accumulating evidence suggests that radixin principally regulates the surface plasma membrane localisation of numerous drug transporters including multidrug resistance protein 2, presumably because radixin is dominantly expressed in the hepatic tissues and cells among ERM proteins [48][49][50][51][52][53]. Therefore, radixin may primarily contribute to the cell surface localisation of PD-L1 in KP-2 cells as a predominant ERM protein, as is the case with ezrin in HeLa, JEG-3, and LS180 cells we have recently reported [29][30][31]. This issue has yet to be unravelled and should be addressed in future studies.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…Accumulating evidence suggests that radixin principally regulates the surface plasma membrane localisation of numerous drug transporters including multidrug resistance protein 2, presumably because radixin is dominantly expressed in the hepatic tissues and cells among ERM proteins [48][49][50][51][52][53]. Therefore, radixin may primarily contribute to the cell surface localisation of PD-L1 in KP-2 cells as a predominant ERM protein, as is the case with ezrin in HeLa, JEG-3, and LS180 cells we have recently reported [29][30][31]. This issue has yet to be unravelled and should be addressed in future studies.…”
Section: Discussionmentioning
confidence: 53%
“…ERM proteins play a pivotal role in the cell surface localisation and functional activity of several cancer-related transmembrane proteins by anchoring them to the plasma membrane via post-translational modification [21,23,25,28]. We recently reported that ezrin functions as a scaffold protein for PD-L1, which leads to the cell surface localisation of PD-L1 in human uterine cervical adenocarcinoma HeLa cells and human choriocarcinoma JEG-3 cells, both of which have the highest expression level of ezrin among ERM protein based on the database analysis utilizing DepMap and/or our experimental data [29,30]. Furthermore, we have found that in human colon adenocarcinoma LS180 cells, ezrin and radixin contributed equally to the cell surface localisation of PD-L1 via physiological interaction and colocalisation with PD-L1, despite extremely low expression level of radixin in LS180 cells [31].…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Immunoprecipitation assays were conducted as previously described [30][31][32][33], with some modifications. Briefly, 500 µL of whole-cell lysates collected in RIPA buffer containing a protease inhibitor cocktail was incubated with 50 µL of protein A beads (nProtein A Sepharose 4 Fast Flow; Cytiva, Tokyo, Japan) on a rotating wheel at 4 • C for 1 h to eliminate non-specific interactions.…”
Section: Immunoprecipitationmentioning
confidence: 99%
“…Furthermore, ERM proteins serve as crosslinkers between several cancer-related transmembrane proteins, including several transmembrane receptor kinases, and the actin cytoskeleton network, contributing to their cell surface localization [27][28][29]. We have recently reported that ERM proteins post-translationally regulate the cell surface localization of PD-L1 by serving as scaffold proteins in different manners in several types of human cancer cells [30][31][32][33][34][35]. However, it remained unclear whether ERM proteins are involved in the cell surface plasma membrane localization of PD-L1 in cervical SCC.…”
Section: Introductionmentioning
confidence: 99%